Management of Inclusive Education: An Implementation - Apriliani, Ike; Pahrudin, Agus; Koderi, Koderi; Syafril, Syafrimen (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to analyze the implementation of inclusive education so that a new concept is found regarding the implementation of inclusive education management that can provide equality for all students. The research method used is qualitative, using data collection techniques through observation, interviews, and documentation. The research results show that: 1) The school has achieved several successes in implementing inclusive education, but there are still several aspects that the school is not fully ready for. 2) Schools have certain strategies for implementing inclusive education, especially by optimizing the role of special guidance teachers to handle children with special needs. 3) The main challenge faced by schools is related to providing programs to develop the potential of children with special needs because, currently, there are no programs available to develop their potential. Data was collected using questionnaire techniques, observation, and interviews. The results of the research show that the implementation of inclusive education has not been optimally implemented; there are still several things that have not even been fulfilled. For this reason, it is hoped that every school will implement inclusive education management under its management steps.